Software Process Improvement 15th European Conference, EuroSPI 2008, Dublin, Ireland, September 3-5, 2008, Proceedings - O'Connor, Rory; Baddoo, Nathan; Smolander, Kari; Messnarz, Richard (Communications in Computer and Information Science, 2008)
This book constitutes the refereed proceedings of the 15th European Conference, EuroSPI 2008, Dublin, Irland, September 2008. The 18 revised full papers presented together with one introductory paper were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on organisational issues; productivity, effort estimation metrics; standards reference models; documentation knowledge management as well as project issues.